2020
DOI: 10.1056/nejmoa2002032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Coronavirus Disease 2019 in China

Abstract: Hypercytokinemia is a critically fatal factor in COVID-19. However, underlying pathogenic mechanisms are unknown. Here we show that brinogen and leukotriene-A4 hydrolase (LTA4H), two of the most potent in ammatory contributors, are elevated by 67.7 and astonishing 227.7% in the plasma of patients infected by SARS-CoV-2 and admitted to intensive care unit in comparison with healthy control, respectively. Conversely, transferrin identi ed as a brinogen immobilizer in our recent work and Spink6 are down-regulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1,724
27,934
367
1,907

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27,099 publications
(33,186 citation statements)
references
References 20 publications
1,724
27,934
367
1,907
Order By: Relevance
“…24 The most common symptoms are fever (87.9%), fatigue (69.6%), dry cough (67.7%) and myalgia (34.8%), and these are accompanied with rhinobyon, rhinorrhoea, pharyngalgia and diarrhea in few patients 24 ( Table 1 ) of these patients were characterized by dyspnea and hypoxemia, which can rapidly progress to acute respiratory distress syndrome (ARDS), septic shock, metabolic acidosis, coagulation dysfunction, and even multiple organ dysfunction syndrome (MODS) in one week. 18,24 Some laboratory tests could provide some hints of the early forms of the disease, such as lymphopenia (82.1%), thrombocytopenia (36.2%) and leukopenia (33.7%). Most patients demonstrated elevated levels of C-reactive protein (CRP).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The most common symptoms are fever (87.9%), fatigue (69.6%), dry cough (67.7%) and myalgia (34.8%), and these are accompanied with rhinobyon, rhinorrhoea, pharyngalgia and diarrhea in few patients 24 ( Table 1 ) of these patients were characterized by dyspnea and hypoxemia, which can rapidly progress to acute respiratory distress syndrome (ARDS), septic shock, metabolic acidosis, coagulation dysfunction, and even multiple organ dysfunction syndrome (MODS) in one week. 18,24 Some laboratory tests could provide some hints of the early forms of the disease, such as lymphopenia (82.1%), thrombocytopenia (36.2%) and leukopenia (33.7%). Most patients demonstrated elevated levels of C-reactive protein (CRP).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…In addition, severe cases could have increasing levels of alanine aminotransferase, aspartate aminotransferase, creatine kinase and creatine. 18,24 All suspected patients are recommended to be examined by chest computerized tomography (CT). Most of the confirmed patients suffered from pneumonia (76.4%), and were characterized with groundglass opacity (50.0%) and bilateral patchy shadowing (46.0%) in the chest CT, and even subsegmental consolidation in severe patients.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), two notable strains of the coronavirus family, are both known to be responsible for severe complications during pregnancy, including the need for endotracheal intubation, admission to an intensive care unit (ICU), renal failure and death 7,8 . In general, both studies reported that the clinical characteristics of the pregnant women with COVID-19 pneumonia were similar to those of non-pregnant adult patients who developed COVID-19 pneumonia [2][3][4] . Chen et al 9 reported the clinical characteristics of nine pregnant women with laboratory-confirmed COVID-19 in the third trimester, which comprised mainly fever and cough.…”
Section: Clinical Manifestation Of Covid-19 Infection During Pregnancymentioning
confidence: 99%
“…14 19 in China, which confirmed the epidemic spreads rapidly by human-to-human transmission and that the disease severity predict poor clinical outcomes. 15 However, the clinical course of the COVID-19 is still not clear. Herein, we collected data from 249 laboratory confirmed cases, aiming to present the clinical progress of the COVID-19.…”
Section: Introductionmentioning
confidence: 99%